The importance of long-term follow-up after EVAR: A case report - Roberta Lozano Gonzalez; Charles Ritchie; Ana Fuentes Perez; Young Erben (Annals of Vascular Surgery - Brief Reports and Innovations, 2022)
Purpose: To report the case of a 78-year-old male patient who underwent repair of a type 1b endoleak (T1bE) fifteen years after endovascular aneurysm repair (EVAR) for an asymptomatic abdominal aortic aneurysm. Case description: A 63-year-old male patient with a 5×4.7 cm asymptomatic abdominal aortic aneurysm (AAA) underwent elective EVAR in 2007. Although on surveillance follow-up one year after the procedure a type 2 endoleak was present, the aneurysm size had decreased to 3.4×3.2 cm. Serial follow-up studies showed caudal migration of the stent-graft without component separation and the aneurysm size progressively increasing, starting at five years after index operation, to a  maximum aneurysm  diameter of 4.7 cm in 2021. Fifteen years after the initial procedure, the patient presented to the emergency department with acute abdominal pain and was found to have an impending rupture of a T1bE. Repair of this endoleak was performed utilizing a through-and-through wire technique from the left brachial to the right common femoral artery for limb graft extension due to tortuosity of the vessels in addition to hypogastric artery embolization. On post-procedural cross-sectional imaging, there was resolution of the endoleak and improvement of his symptoms. Conclusion: Although T1bE are extremely rare, their presence requires immediate attention due to the risk for rupture. Attentive and serial follow-up including long-term surveillance are necessary in patients after EVAR since reintervention can occur even years after initial repair.